Клініко-лабораторна характеристика вітамін D-дефіцитного рахіту у дітей раннього віку при ожирінні = Clinical-laboratory characteristics of vitamin D-deficient rickets in infants with obesity - Тokarchuk N. I.; Pugach, M. M.; Chekotun, T. V.; Starinetz, L. S.; Savicka, T. V.; Lagoda, V. V. (Journal of Education, Health and Sport, 2015)
Тokarchuk N. I., Pugach M. М., Chekotun Т. V., Starinetz L. S., Savicka T. V., Lagoda V. V. Клініко-лабораторна характеристика вітамін D-дефіцитного рахіту у дітей раннього віку при ожирінні = Clinical-laboratory characteristics of vitamin D-deficient rickets in infants with obesity. Journal of Education, Health and Sport. 2015;5(11):111-116. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33536 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A111-116 https://pbn.nauka.gov.pl/works/667735 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. КЛІНІКО-ЛАБОРАТОРНА ХАРАКТЕРИСТИКА ВІТАМІН D-ДЕФІЦИТНОГО РАХІТУ У ДІТЕЙ РАННЬОГО ВІКУ ПРИ ОЖИРІННІ CLINICAL-LABORATORY CHARACTERISTICS OF VITAMIN D-DEFICIENT RICKETS IN INFANTS WITH OBESITY Н.І. Токарчук¹, М.М. Пугач¹, Т.В. Чекотун¹, Л.С. Старинець², Т.В. Савицька², В.В. Лагода² N. I. Тokarchuk¹, M. М. Pugach¹, Т. V. Chekotun¹, L. S. Starinetz², T. V. Savicka², V. V. Lagoda² ¹Вінницький національний медичний університет ім. М. І. Пирогова, Україна ²Вінницька обласна дитяча клінічна лікарня, Україна ¹N.I. Pirogov Vinnitsa National Medical University, Ukraine ²Regional Children’s Hospital Vinnitsa, Ukraine Abstract The study involved 120 infants suffering from vitamin D-deficient rickets which were divided into subgroups based on physical development indicators. We conducted a clinical examination of children anamnesis, and determined serum concentrations of 25 (OH) D. While studying in what way vitamin D-deficient rickets severity in infants depends of physical development indicators, we found increase in severity of rachitic process according to increasing values of body weight. Thus, the largest proportion of medium severity cases of vitamin D-deficient rickets was determined in children who were obese. In infants with rickets, the lowest vitamin D status was registered against the background of obesity. This aspect is possibly predetermined by the influence of endogenous pathogenic factors in the state of obesity due to the deposit of vitamin D in adipose tissue. Key words: vitamin D-deficient rickets, obesity, infants, hydroxyvitamin D. Резюме У дослідженні прийняли участь 120 дітей першого року життя, хворі на вітамін D-дефіцитний рахіт, і були розподілені на підгрупи залежно від показників фізичного розвитку. Нами проведено клініко-анамнестичне обстеження дітей та визначення в сироватці крові концентрації 25(OH)D. При вивченні залежності ступеня тяжкості вітамін D-дефіцитного рахіту у дітей першого року життя від показників фізичного розвитку, нами виявлено зростання тяжкості рахітичного процесу відповідно до збільшення значень маси тіла. Так, найбільша питома вага випадків середнього ступеня важкості вітамін D-дефіцитного рахіту констатована у дітей, які мали ожиріння. У дітей першого року життя, хворих на рахіт, найнижчий статус вітаміну D було зареєстровано на тлі ожиріння. Даний аспект, можливо, обумовлений впливом патогенетичних ендогенних факторів при ожирінні за рахунок депонування вітаміну D в жировій тканині. Ключові слова: вітамін D-дефіцитний рахіт, ожиріння, діти раннього віку, гідроксивітамін D.